Necrotizing Enterocolitis among Newborn Infants Suffering from Gastroenteritis: A Clinical evaluation of 17 cases - Muzief Munir; Tjandra Husada; Soeharno Soeharno; Nurhidayat Nurhidayat (Indonesian Pediatric Society, 1980)
Seventeen infants with NNEC were evaluated. The diagnosis was based on clinical, laboratory and rontgenographic findings. Twelve out of them had a low birth weight (less than 2500 grams) and 5 were prematures. Since only 2 cases had asphyxia at 1 minute after birth, asphyxia apparently played only a small role as the perinatal factor in the development of NNEC. Besides gastroenteritis, bronchopneumonia and meningitis were the accompanying diseases in 2 cases and 1 case respectively. Bacterial findings from the stool and cerebrospinal fluid were as follows: E. Coli 0111 K 58 (b), 0126 K 71 (B) H2 were cultured from the stool of 7 infants; Pseudomonas from cerebrospinal fluid was found in 1 case. Prior to the onset of symptoms, all of these infants were fed with milk formula. Therefore the authors believe that infections and formula feedings play an important role in the development of NNEC. The survival rate of our cases was poor with 52% deaths (9 out of 17), and 2 of them had intestinal perforation. Anemia which develops rapidly should be taken into account in the management of NNEC.